TWO DIMENSIONAL MODELING OF GRAVITY DATA AT LEMBANG FAULT ZONE - DIANA MURTI (NIM : 10212003), MULYA
Gravity method is one of geophysical method that can be used to detecting under subsurface rock density. In this final project, gravity method was applied at Lembang fault area located in Kabupaten Bandung. Lembang fault is an active fault that potentialy make an earthquake. The purpose of this research is detecting Lembang fault's stuctures and fault geometries using geophysical method: gravity. Survey using gravity method had been done with the north to south that crossed Lembang fault in 24 point. Based to field measured data, many corrections aplied until getting complete bouger anomaly range from -919.328 mGal to -652.491 mGal that represented the difference of subsurface density. After that forward modelling 2D had been done to saw subsurface anomaly response. According to result of forward modelling at research area, there is a normal fault. It is indicated by there is significant contrast density under subsurface.